PEMBIAYAAN MELALUI FINTECH SYARI’AH SEBAGAI UPAYA PENGEMBANGAN UMKM DI ERA KEUANGAN DIGITAL - Aji Nuryakin, Rahmat; Jumiati, Eti; Solihin, Asep; Saefuddin, Aep; Rahayu, Wati (Program Studi Ekonomi Syariah, 2025)
This study aims to describe the distribution of funding through Financial Technology (Fintech) Syari'ah in an effort to develop MSMEs in the current Disruption Innovation era in Indonesia. The method used for this research is descriptive analysis with an exploratory qualitative approach in order to understand an event, ensure the validity of the data, categorize the data, and construct the phenomena that occur. The data collected is secondary data, technical analysis and data collection is carried out by literature review as data to support scientific research. The data analyzed are in the form of journals, scientific papers, articles, official websites of Fintech companies, and other required sources. The results of the literature data can help identify whether Syari'ah Fintech is an alternative to MSME funding that does not have business capital reserves with a scheme according to a contract in Shari'ah principles and the extent of the role of Syari'ah Fintech in helping MSME financing in Indonesia